2007
DOI: 10.1111/j.1467-7652.2007.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination: a basis for targeted genome optimization in crop species such as maize

Abstract: SummaryIn an attempt to understand the feasibility of future targeted genome optimization in agronomic crops, we tested the efficiency of homologous recombination-mediated sequence insertion upon induction of a targeted DNA double-strand break at the desired integration site in maize. By the development of an efficient tissue culture protocol, and with the use of an I-Sce I gene optimized for expression in maize, large numbers of precisely engineered maize events were produced in which DNA integration occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 35 publications
2
66
0
Order By: Relevance
“…Mutations of artificially introduced I-SceI recognition site in maize (Zea mays) were detected in 1% of analyzed F1 plants when I-SceI was introduced by crossing and activated by gene excision (Yang et al, 2009). Through the codelivery of a donor and an I-SceI expression DNA by either A. tumefaciens or biolistic transformation, the 35S promoter of the donor DNA was precisely inserted at previously introduced I-SceI sites at practical frequencies (D'Halluin et al, 2008).…”
mentioning
confidence: 99%
“…Mutations of artificially introduced I-SceI recognition site in maize (Zea mays) were detected in 1% of analyzed F1 plants when I-SceI was introduced by crossing and activated by gene excision (Yang et al, 2009). Through the codelivery of a donor and an I-SceI expression DNA by either A. tumefaciens or biolistic transformation, the 35S promoter of the donor DNA was precisely inserted at previously introduced I-SceI sites at practical frequencies (D'Halluin et al, 2008).…”
mentioning
confidence: 99%
“…Similar results were obtained using a dexamethasone-inducible I-SceI enzyme and induction of I-SceI under the speci fi c Apetala3 fl oral promoter speci fi cally enhanced germinal recombination events up to 4-fold. The integration of extrachromosomal DNA through HR at a speci fi c I-SceI target site has also been shown in Maize (D'Halluin et al 2008 ) . The authors optimised an I-SceI gene for expression in maize and showed induction of homologous recombination-mediated insertion at the desired site after DSB induction.…”
Section: I-scei Meganucleasementioning
confidence: 95%
“…Transient expression of SDN: To date, examples of co-delivery of the SDN and donor DNA for transient expression include electroporation of tobacco protoplasts (Wright et al, 2005), Agrobacterium-mediated transformation of tobacco protoplasts and tobacco leaf discs (Cai et al, 2009), biolistics or Agrobacterium-mediated transformation of maize suspension cells (D'Halluin et al, 2008), and whisker-mediated transformation of maize embryos (Shukla et al, 2009 [de Pater et al, 2009]). The excision and reinsertion "in planta" into a targeted locus of a transgene already present in the plant has been achieved in Arabidopsis (Fauser et al, 2012).…”
Section: Donor Dna Delivery Mechanism and Expression Of Sdnsmentioning
confidence: 99%
“…In this experiment more than 10 % of the transformed protoplasts contained the transgene at the target locus regardless of the chromosomal position of the target. In maize, co-delivery of the transgene and the DNA encoding the I-SceI MN was achieved using either biolistics or Agrobacterium-mediated transformation (D'Halluin et al, 2008) and the presence of the I-SceI MN led to an estimated 14 to 30 000-fold increase in the frequency of targeted versus random integration of the transgene. The variation in increase of gene targeting efficiency was dependent on the technique of DNA delivery used and on the artificial target site selected.…”
Section: Targeted Integration Of Donor Dna Via Homologous Recombinationmentioning
confidence: 99%